Usability evaluation dimension for academic digital libraries: a review/ Razilan A. Kadir ...[et al.] - A. Kadir, Razilan; Wan Dollah, Wan Ab. Kadir; Jamaludin, Adnan; Singh, Diljot (Faculty of Information Management, Universiti Teknologi MARA, 2011)
Explosion in information and information system (JS) technology has brought dramatic changes in learning and library system environments. Through the passage from physical library to digital library era, the use of academic digital library systems do witness spectacular impact on academic societies' way of performing their study/research. Thus, evaluating the system is of paramount importance in understanding how useful it is and how it can be beneficial for its targeted community. Usability design approach is widely used in the literature for evaluating digital libraries. In this article, we review and examine the usability dimensions in usability evaluation for digital libraries. Based on the literature, usability engineering model is one of usability models applied in the context of human-computer-interaction basis. This article reviews on this usability engineering model that defines interface usability dimensions idea together with its extended version to organizational usability dimension. Both of these usability dimensions, interface and organizational, are potential in evaluating academic digital library, from the perspective of the users' requirements, as well as from the academic institutions' requirements